2006
DOI: 10.1021/jf0581269
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of 14C-Phytoene from Tomato Cell Suspension Cultures (Lycopersicon esculentum) for Utilization in Prostate Cancer Cell Culture Studies

Abstract: This work describes the development and utilization of a plant cell culture production approach to biosynthesize and radiolabel phytoene and phytofluene for prostate cancer cell culture studies. The herbicide norflurazon was added to established cell suspension cultures of tomato (Lycopersicon esculentum cv. VFNT cherry), to induce the biosynthesis and accumulation of the lycopene precursors, phytoene and phytofluene, in their natural isomeric forms (15-cis-phytoene and two cis-phytofluene isomers). Norflurazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(88 citation statements)
references
References 48 publications
3
85
0
Order By: Relevance
“…This subject has been studied in detail cyanobacteria, algae and plants [82][83][84][85][86][87]. In a novel approach, norflurazon has been used in tomato cell cultures containing 14C-sucrose in the medium to produce 14C-labeled phytoene to gain further insight into the bioavailability and biological actions of this carotenoid [88].…”
Section: Plantsmentioning
confidence: 99%
“…This subject has been studied in detail cyanobacteria, algae and plants [82][83][84][85][86][87]. In a novel approach, norflurazon has been used in tomato cell cultures containing 14C-sucrose in the medium to produce 14C-labeled phytoene to gain further insight into the bioavailability and biological actions of this carotenoid [88].…”
Section: Plantsmentioning
confidence: 99%
“…LYC was the predominant carotenoid in the seminal vesicles, ventral, dorsolateral, and anterior prostate lobes when rats were fed tomato powder, yet measurable quantities of PE, PF, and ζ-carotene were also present. Recently, we have also shown that 14 C-phytoene accumulates in human DU 145 prostate cancer cells after a 2 d incubation period [17]. In human prostate, LYC is the most abundant carotenoid [10,27], but a variety of other tomato carotenoids also accumulate [10,14].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should focus on the in vivo metabolism of PE and PF in a similar manner to studies that have been accomplished for LYC metabolism [16,46]. As 14 C-PE and 14 C-PF sources are not available, biosynthesis of these and other carotenoids through in vitro plant cell culture methodologies is necessary [17]. Precise qualitative and quantitative identification of 14 Ccarotenoid metabolites throughout the body, with an emphasis on the prostate [16,46], are essential to evaluate potential mechanisms of actions by which tomato carotenoids may act in prostate cancer prevention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Separate quantification of lutein and zeaxanthin is essential to investigate their individual roles in age-related macular degeneration [7]. The polymeric C30 columns possess unique abilities to resolve cis/trans-carotenoids and are widely adopted for analysis in biological extracts [6,[15][16][17][18]. In a study dealing with quantitation of cis-and trans-carotenoids in human blood of Taiwan subjects, Rajendran et al [6] developed a HPLC method and separated 21 cis plus trans carotenoids within 51 min by using a polymeric C30 column and a gradient mobile phase.…”
Section: Introductionmentioning
confidence: 99%